GE_GERICHTE P/191/2021 vom 14. Oktober 2021 - GE Cour de justice (2021)
DISPOSITIONS PÉNALES DE LA LCR;CONTRAINTE(DROIT PÉNAL);CHANTAGE;TENTATIVE(DROIT PÉNAL);FIXATION DE LA PEINE;EXPULSION(DROIT PÉNAL) | LCR.90; LCR.91; LCR.92; LCR.95; CP.286; CP.156; CP.181; CP.47; CP.49; CP.41; CP.34; CP.66abis